Optimization of Vapor Compression Refrigeration Cycles with Clathrate Hydrates Thermal Energy Storage - Gadalla, Akram Mohamed (2021)
A Master of Science thesis in Mechanical Engineering by Akram Mohamed Gadalla entitled, “Optimization of Vapor Compression Refrigeration Cycles with Clathrate Hydrates Thermal Energy Storage”, submitted in December 2021. Thesis advisor is Dr. Mohamed Omar Abdelgawad. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).